New species of Anchastus LeConte, 1853 from South America (Elateridae, Elaterinae, Ampedini, Physorhinina) - Casari, Sônia A. (Zootaxa, 2015)
Seven new species of Anchastus LeConte, 1853 are described: A. brunneifinibus sp. nov. (Bolivia), A. cuiabanus sp. nov. (Brazil), A. flavonigrothoracicum sp. nov. (Bolivia), A. rubrithoracicum sp. nov. (Brazil, Bolivia), A. thoracoferrugineus sp. nov. (Bolivia), A. transverseplagiatus sp. nov. (Bolivia) and A. uniplagipennis sp. nov. (Bolivia). The female genitalia of A. boulardi Chassain, 2010 is described and three species are redescribed: A. moratus (Candèze, 1863) (Mexico, Guyana, Brazil, Bolivia), A. quadrimaculatus Candèze, 1889 (Guyana, Brazil, Bolivia) and A. unitinctus Candèze, 1889 (Brazil). New records for A. touroulti Chassain, 2010 are presented. A provisional identification key for South American species is provided.